Modelling of vehicle motion - Listopadskis, Narimantas (Lietuvos matematikos rinkinys, 2000)
The problem is to calculate the path trajectory for a vehicle following a wire in the floor. Motion of the vehicle is determined by system of differential equations. Fourth-order Runge-Kutta adaptive method was used for solving of the obtained systems of the differential equations.